High-refractive high-dispersion optical glass, glass preform, optical element, and optical instrument
Patent Information
- Application Number
- CN202611232227.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-14
- Publication Date
- 2026-10-27
AI Technical Summary
为将光学玻璃应用于各种光学仪器中,需将光学玻璃进行加工或清洗,若光学玻璃的化学稳定性差,则在加工或清洗过程中玻璃容易出现潮解或腐蚀,影响光学仪器的成像质量
[0018]本申请的有益效果是:通过合理的组分设计,本申请获得的光学玻璃在具有期望的折射率和阿贝数的同时,还具有优异的化学稳定性,可广泛应用于各种高性能光学仪器中。
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This application relates to the field of optical glass technology, and in particular to a high-refractive-index, high-dispersion optical glass with excellent chemical stability, as well as glass preforms, optical elements and optical instruments made therefrom. Background Technology
[0002] In recent years, with the rapid development of optoelectronic information, digital display, surveillance and security, and automotive imaging, there has been a growing demand for miniaturization, lightweighting, and high performance in optical components used in optical systems. High-refractive-index, high-dispersion optical glass can be coupled with low-dispersion optical glass to effectively eliminate chromatic aberration and secondary spectral distortion. Simultaneously, it can effectively shorten the overall optical length of the lens, enabling miniaturization of the imaging system. Therefore, this type of glass has a very broad application prospect. For the same radius of curvature, glass with a higher refractive index obtains a larger imaging field of view, which is beneficial for reducing the number of optical components in optical instruments. With the trend of miniaturization in optical instruments, the demand for high-refractive-index, high-dispersion optical glass continues to increase. To apply optical glass to various optical instruments, it needs to be processed or cleaned. If the optical glass has poor chemical stability, it is prone to deliquescence or corrosion during processing or cleaning, affecting the imaging quality of the optical instrument. Summary of the Invention
[0003] The technical problem to be solved by this application is to provide a high-refractive-index, high-dispersion optical glass with excellent chemical stability, as well as glass preforms, optical elements and optical instruments made therefrom.
[0004] The technical solution adopted by this application to solve the technical problem is:
[0005] The high-refractive-index, high-dispersion optical glass contains, by weight percentage: SiO2: 15%–35%; Nb2O5: 33%–55%; Na2O: 2%–10%; ZrO2: 2%–10%; TiO2: 2%–12%; Li2O: 0–10%; ZnO: greater than 0 but less than or equal to 5%, wherein ZnO / (Na2O+Li2O) is 0.02–0.35.
[0006] In some embodiments, the high-refractive-index, high-dispersion optical glass, whose components are expressed as weight percentages, further contains: P2O5: 0–5%; and / or RO: 0–5%; and / or K2O: 0–5%; and / or WO3: 0–5%; and / or Re2O3: 0–1%; and / or clarifying agent: 0–1%, wherein the RO is one or more of MgO, CaO, SrO, and BaO, the Re2O3 is one or more of La2O3, Y2O3, and Gd2O3, and the clarifying agent is one or more of Sb2O3, SnO, SnO2, and CeO2.
[0007] The high-refractive-index, high-dispersion optical glass comprises SiO2, Nb2O5, Na2O, ZrO2, TiO2, and ZnO, expressed as a weight percentage, and contains 0–10% Li2O, wherein the ZnO / (Na2O+Li2O) ratio is 0.02–0.35. The refractive index n of the high-refractive-index, high-dispersion optical glass is... d The Abbe number ν ranges from 1.82 to 1.89. d The stability of the acid resistance is 21-28. A Class 2 or above, water resistance stability D W It is classified as category 2 or above.
[0008] In some embodiments, the high-refractive-index, high-dispersion optical glass comprises, by weight percentage: SiO2: 15%–35%; and / or Nb2O5: 33%–55%; and / or Na2O: 2%–10%; and / or ZrO2: 2%–10%; and / or TiO2: 2%–12%; and / or ZnO: greater than 0 but less than or equal to 5%; and / or P2O5: 0–5%; and / or RO: 0–5%; and / or K2O: 0–5%; and / or WO3: 0–5%; and / or Re2O3: 0–1%; and / or clarifying agent: 0–1%, wherein RO is one or more of MgO, CaO, SrO, and BaO, Re2O3 is one or more of La2O3, Y2O3, and Gd2O3, and the clarifying agent is one or more of Sb2O3, SnO, SnO2, and CeO2.
[0009] In some embodiments, the high-refractive-index, high-dispersion optical glass has a composition expressed as a weight percentage, wherein ZnO / (Na2O+Li2O) is 0.05 to 0.30, and optionally ZnO / (Na2O+Li2O) is 0.06 to 0.27.
[0010] In some embodiments, the high-refractive-index, high-dispersion optical glass has a composition expressed as a weight percentage, wherein: TiO2 / Nb2O5 is 0.05 to 0.30, optionally TiO2 / Nb2O5 is 0.08 to 0.27, and more preferably TiO2 / Nb2O5 is 0.10 to 0.24.
[0011] In some embodiments, the high-refractive-index, high-dispersion optical glass has a composition expressed as a weight percentage, wherein (TiO2+Nb2O5) / (SiO2+ZrO2+ZnO) is 0.75 to 2.50, optionally (TiO2+Nb2O5) / (SiO2+ZrO2+ZnO) is 0.80 to 2.20, and more preferably (TiO2+Nb2O5) / (SiO2+ZrO2+ZnO) is 1.11 to 1.96.
[0012] In some embodiments, the high-refractive-index, high-dispersion optical glass has a composition expressed as a weight percentage, wherein (P2O5+ZnO) / SiO2 is 0.01 to 0.35, optionally (P2O5+ZnO) / SiO2 is 0.02 to 0.30, and more preferably (P2O5+ZnO) / SiO2 is 0.04 to 0.24.
[0013] In some embodiments, the high-refractive-index, high-dispersion optical glass comprises, by weight percentage: SiO2: 17%–33%, optionally SiO2: 18%–30%; and / or Nb2O5: 34%–53%, optionally Nb2O5: 35%–50%; and / or Na2O: 3%–9%, optionally Na2O: 4%–8%; and / or ZrO2: 3%–9%, optionally ZrO2: 4%–8%; and / or TiO2: 3%–11%, optionally TiO2: 4%–10%; and / or Li2O: 1%–9%, optionally Li2O: 2%–7%; and / or ZnO: 0.2%–4%, optionally ZnO: 0.5%–3%; and / or P2O5: 0.2%–3%, optional P2O5: 0.3%–2%; and / or RO: 0–4%, optional RO: 0–3%; and / or K2O: 0–4%, optional K2O: 0–3%; and / or WO3: 0–4%, optional WO3: 0–3%; and / or Re2O3: 0–0.8%, optional Re2O3: 0–0.5%; and / or clarifying agent: 0–0.5%, optional clarifying agent: 0–0.2%, wherein the RO is one or more of MgO, CaO, SrO, and BaO, the Re2O3 is one or more of La2O3, Y2O3, and Gd2O3, and the clarifying agent is one or more of Sb2O3, SnO, SnO2, and CeO2.
[0014] In some embodiments, the refractive index n of the high-refractive-high-dispersion optical glass d The range is 1.82–1.89, with an optional range of 1.83–1.88, and even more preferably 1.84–1.87; and / or the Abbe number ν. d The value is 21–28, optionally 22–27, and even more preferably 23–26; and / or acid resistance stability D. A If there are two or more categories, one category may be selected; and / or water resistance stability D W If there are two or more classes, one class can be selected; and / or partial dispersion ratio P g,F The coefficient of thermal expansion is 0.6050–0.6200, and can be selected as 0.6070–0.6180; and / or the anti-crystallization performance is grade B or above, and can be selected as grade A; and / or the coefficient of thermal expansion α 100℃ / 300℃ 80×10 -7 / K~120×10 -7 / K, optional 85×10 -7 / K~115×10 -7 / K, or 90×10 -7 / K~110×10 -7 / K; and / or transition temperature T g Temperature is below 610℃, optionally below 600℃, and even more preferably below 590℃; and / or density ρ is 3.80 g / cm³. 3 The following can be selected as 3.70 g / cm³. 3 The following is an alternative option: 3.60 g / cm³ 3 The following; and / or chromaticity λ 70 The wavelength is below 430nm, optionally below 425nm, and even more preferably below 420nm; and / or the bubble density is A grade or above, optionally above A0 grade, and even more preferably A. 00 class.
[0015] The glass preform is made of the aforementioned high-refractive-index, high-dispersion optical glass.
[0016] The optical element is made of the aforementioned high-refractive-index, high-dispersion optical glass, or of the aforementioned glass preform.
[0017] An optical instrument comprising the aforementioned high-refractive-index, high-dispersion optical glass, and / or comprising the aforementioned optical elements.
[0018] The beneficial effects of this application are: through reasonable component design, the optical glass obtained by this application has excellent chemical stability while having the desired refractive index and Abbe number, and can be widely used in various high-performance optical instruments. Detailed Implementation
[0019] The embodiments of this application will now be described in detail. However, this application is not limited to the embodiments described below, and appropriate modifications can be made to implement it within the scope of the purpose of this application. Furthermore, regarding repeated descriptions, although there are appropriate omissions, this will not limit the spirit of the application. In the following text, the high-refractive-index, high-dispersion optical glass of this application may be simply referred to as optical glass or glass.
[0020] High-refractive-index, high-dispersion optical glass
[0021] The composition range of each component in the high-refractive-index, high-dispersion optical glass of this application is described below. In this application, unless otherwise specified, the content of each component, the total content, and the total content are all expressed as weight percentages (wt%), that is, the weight percentage of the content of each component, the total content, and the total content relative to the total amount of glass material converted into oxide composition. Here, "converted into oxide composition" refers to the total amount of oxides used as raw materials for the optical glass of this application, where the oxides, complex salts, and hydroxides decompose and transform into oxides upon melting, and the total amount of such oxides is taken as 100%.
[0022] Unless otherwise specified in the specific circumstances, the numerical ranges listed in this application include upper and lower limits, and "above" and "below" include endpoint values and all integers and fractions included in the range, but are not limited to the specific values listed when the range is defined. The term "and / or" as used herein is inclusive; for example, "A and / or B" means only A, or only B, or both A and B.
[0023] <Essential and Optional Components>
[0024] In this application, SiO2 is a network-forming component of the glass, playing a role in maintaining glass stability and suitable viscosity for molten glass forming. However, if the SiO2 content is too high, it will lead to a decrease in the glass's refractive index, high high-temperature viscosity, and poor melting performance; if the SiO2 content is too low, it will lead to a decrease in the glass's resistance to crystallization and a tendency for streaks to appear. Therefore, the SiO2 content is 15% to 35%, optionally 17% to 33%, and more preferably 18% to 30%.
[0025] In this application, Nb₂O₅ is a network-forming component of the glass, which improves the refractive index and reduces the partial dispersion ratio of the glass. However, if the Nb₂O₅ content is too high, it will lead to a decrease in the glass's resistance to crystallization and an increase in its high-temperature viscosity, making melting more difficult; if the Nb₂O₅ content is too low, it will be difficult for the glass to achieve the design refractive index, and the chemical stability of the glass will decrease. Therefore, the Nb₂O₅ content is 33% to 55%, optionally 34% to 53%, and more preferably 35% to 50%.
[0026] In this application, TiO2 is a network-forming component of the glass, which increases the refractive index and reduces the Abbe number, while also optimizing anti-crystallization properties. However, if the TiO2 content is too high, it will lead to an increase in the partial dispersion ratio of the glass, making it difficult to achieve the desired specific dispersion properties, and will also cause the glass color to darken due to the change in titanium valence. Therefore, the TiO2 content is 2%–12%, optionally 3%–11%, and more preferably 4%–10%.
[0027] In some embodiments, by controlling the ratio of TiO2 content to Nb2O5 content (TiO2 / Nb2O5) within the range of 0.05 to 0.30, the glass can have a suitable partial dispersion ratio and visible light transmittance, preventing a deterioration in the glass's anti-crystallization properties. Therefore, a TiO2 / Nb2O5 ratio of 0.05 to 0.30 is preferable, more preferably 0.08 to 0.27, and even more preferably 0.10 to 0.24.
[0028] Na₂O is an alkali metal oxide with a strong fluxing effect, which helps to break down the dense network structure of glass, allowing more high-refractive components to incorporate into the glass and making it easier to achieve a higher refractive index. It can also reduce the high-temperature viscosity and transition temperature of molten glass. However, excessive Na₂O content can easily lead to a decrease in the chemical stability and anti-crystallization properties of the glass. Therefore, in this application, the Na₂O content is 2%–10%, optionally 3%–9%, and more preferably 4%–8%.
[0029] ZrO2 can increase the refractive index of glass and regulate dispersion, while also reducing the partial dispersion ratio and inhibiting crystallization. However, excessive ZrO2 content can lead to an increase in the glass melting temperature, and due to its relatively high density, it can easily cause phase separation and precipitation in the molten glass during melting. Therefore, the ZrO2 content is typically 2%–10%, with 3%–9% being a more suitable option, and even more suitable at 4%–8%.
[0030] Li₂O, an alkali metal oxide, can reduce the high-temperature viscosity of glass, improve its melting properties, optimize its resistance to crystallization, and disperse the glass framework, allowing for a greater inclusion of specific dispersive components. However, higher Li₂O content increases the raw material cost and reduces the glass's chemical stability. Therefore, the Li₂O content is typically 0–10%, with a maximum of 1%–9%, and ideally 2%–7%.
[0031] In this application, ZnO plays a role in stabilizing the glass network, which helps to improve the transmittance of the glass in the visible light band and enhance its resistance to crystallization. However, when its content is too high, the glass's resistance to crystallization decreases, and the viscosity of the glass becomes too low, increasing the difficulty of molding. Therefore, the ZnO content is greater than 0 but less than or equal to 5%, preferably 0.2% to 4%, and more preferably 0.5% to 3%.
[0032] In some embodiments, by controlling the ratio of ZnO content to the total content of Na2O and Li2O (Na2O+Li2O), ZnO / (Na2O+Li2O), within the range of 0.02 to 0.35, the glass can have a suitable high-temperature viscosity, optimize the glass-forming properties, and prevent the glass density from increasing and the chemical stability from deteriorating. Therefore, ZnO / (Na2O+Li2O) can be selected as 0.02 to 0.35, more preferably 0.05 to 0.30, and even more preferably 0.06 to 0.27.
[0033] In some embodiments, by controlling the ratio of the total content of TiO2 and Nb2O5 (TiO2+Nb2O5) to the total content of SiO2, ZrO2 and ZnO (SiO2+ZrO2+ZnO) (TiO2+Nb2O5) / (SiO2+ZrO2+ZnO) within the range of 0.75 to 2.50, the glass can easily obtain the desired high refractive index and low Abbe number while having good glass-forming properties, visible light transmittance, and a suitable coefficient of thermal expansion. Therefore, the ratio of (TiO2+Nb2O5) / (SiO2+ZrO2+ZnO) can be selected as 0.75~2.50, more preferably (TiO2+Nb2O5) / (SiO2+ZrO2+ZnO) can be selected as 0.80~2.20, and even more preferably (TiO2+Nb2O5) / (SiO2+ZrO2+ZnO) can be selected as 1.11~1.96.
[0034] In this application, P2O5 helps to adjust the viscosity of the glass, disperses the glass network, increases the solubility of special dispersive components, and is beneficial for reducing the partial dispersion ratio of the glass. However, when the P2O5 content is too high, the glass's resistance to crystallization decreases, and phase separation easily occurs in the molten glass during the melting process. Therefore, the P2O5 content is 0-5%, preferably 0.2%-3%, and more preferably 0.3%-2%.
[0035] In some embodiments, by controlling the ratio of the total content of P2O5 and ZnO (P2O5+ZnO) to the content of SiO2 (P2O5+ZnO) / SiO2 within the range of 0.01 to 0.35, the glass can maintain good anti-crystallization properties and chemical stability while preventing phase separation and bubbles, and preventing a decrease in the streaking and bubble count grades. Therefore, (P2O5+ZnO) / SiO2 can be selected as 0.01 to 0.35, more preferably 0.02 to 0.30, and even more preferably 0.04 to 0.24.
[0036] RO (RO can be one or more of MgO, CaO, SrO, and BaO) can improve the melting properties of glass and lower its transition temperature; however, if the RO content is too high, glass components are prone to precipitation, and the glass's resistance to crystallization decreases. Therefore, the RO content is 0–5%, preferably 0–4%, or even 0–3%.
[0037] K₂O is an alkali metal component that reduces glass viscosity and improves glass melt properties; however, when its content is too high, the glass's resistance to crystallization decreases and its chemical stability deteriorates. Therefore, the K₂O content is 0–5%, preferably 0–4%, and even more preferably 0–3%.
[0038] WO3 can increase the refractive index of glass and lower its transition temperature, but if its content is too high, the coefficient of thermal expansion of the glass will increase, the thermal stability will decrease, and the dispersion ratio will increase. Therefore, the WO3 content is 0-5%, preferably 0-4%, or even 0-3%.
[0039] Re2O3 (which can be one or more of La2O3, Y2O3, and Gd2O3) is a high-refractive-index, low-dispersion component that can increase the refractive index and reduce the high-temperature viscosity of glass. However, when its content is high, the Abbe number of the glass is high, and its resistance to crystallization decreases. Therefore, the content of Re2O3 is 0-1%, preferably 0-0.8%, and even more preferably 0-0.5%.
[0040] In this application, one or more of the following components—Sb₂O₃, SnO, SnO₂, and CeO₂—are used as clarifying agents, which can improve the clarification effect of the glass. The content of the clarifying agent can be selected as 0-0.5%, more preferably 0-0.2%. When the Sb₂O₃ content exceeds 1%, the glass tends to have reduced clarification performance. Simultaneously, its strong oxidizing effect promotes the corrosion of platinum or platinum alloy vessels used in the molten glass and the deterioration of the forming mold. Therefore, the content of Sb₂O₃ in this application can be selected as 0-1%, more preferably 0-0.5%, and even more preferably 0-0.2%. SnO and SnO₂ can also be used as clarifying agents, but when their content exceeds 1%, the tendency for glass coloring increases. Alternatively, when the glass is heated, softened, and then molded, Sn can become the starting point for crystal nucleation, leading to a tendency for devitrification. Therefore, the SnO2 content in this application can be selected as 0-1%, more preferably 0-0.5%, further preferably 0-0.2%, and even more preferably without SnO2; the SnO content can be selected as 0-1%, more preferably 0-0.5%, further preferably 0-0.2%, and even more preferably without SnO. The role of CeO2 is similar to that of SnO2, and its content can be selected as 0-1%, more preferably 0-0.5%, further preferably 0-0.2%, and even more preferably without CeO2.
[0041] <Components that should not be present>
[0042] In the glass of this application, even if oxides of transition metals such as V, Cr, Mn, Fe, Co, Ni, Cu, Ag, and Mo are contained in small amounts, either alone or in combination, the glass will be colored and absorb at specific wavelengths in the visible light region, thereby weakening the property of this application to improve visible light transmittance. Therefore, it is preferable to omit these oxides, especially for optical glass that requires transmittance in the visible light region.
[0043] Oxides of Th, Cd, Tl, Os, Be, and Se have been increasingly subject to controlled use in recent years due to their status as hazardous chemicals. Environmental protection measures are essential not only in glass manufacturing but also in processing and post-product disposal. Therefore, given the importance of environmental impact, it is preferable to eliminate these substances, except where their contamination is unavoidable. Consequently, the optical glass becomes virtually free of pollutants. Therefore, even without specific environmental countermeasures, the optical glass of this application can be manufactured, processed, and disposed of.
[0044] To achieve environmental friendliness, the optical glass in this application may be free of As2O3 and PbO.
[0045] The terms "not containing", "0", and "0%" used herein refer to the fact that the compound, molecule, or element was not intentionally added to the optical glass of this application as a raw material. However, as raw materials and / or equipment used in the production of optical glass, there may be certain impurities or components that are not intentionally added, which may be present in small amounts or trace amounts (less than 0.01%) in the final optical glass. Such cases are also within the scope of protection of this patent application.
[0046] The performance of the high-refractive-index, high-dispersion optical glass of this application will now be described.
[0047] <Refractive Index and Abbe Number>
[0048] The refractive index (n) of optical glass d ) and Abbe number (ν) d Tested according to the method specified in the national standard GB / T 7962.1—2010.
[0049] In some embodiments, the refractive index (n) of the high-refractive-index, high-dispersion optical glass of this application is... d The lower limit is 1.82, the optional lower limit is 1.83, and the more optional lower limit is 1.84.
[0050] In some embodiments, the refractive index (n) of the high-refractive-index, high-dispersion optical glass of this application is... d The maximum value is 1.89, the maximum optional value is 1.88, and the maximum further optional value is 1.87.
[0051] In some embodiments, the Abbe number (ν) of the high-refractive-index, high-dispersion optical glass of this application is... d The lower limit of ) is 21, the optional lower limit is 22, and the more optional lower limit is 23.
[0052] In some embodiments, the Abbe number (ν) of the high-refractive-index, high-dispersion optical glass of this application is... d The maximum number of options is 28, the maximum number of optional options is 27, and the maximum number of further optional options is 26.
[0053] Partial Dispersion Ratio
[0054] Partial dispersion ratio (P) of optical glass g,F ) represents partial dispersion (n g -n F ) relative to the principal dispersion (n F -n C The ratio of n to n can be obtained from the following formula (1). g This represents the refractive index of the glass for light with a wavelength of 435.835 nm.
[0055] P g,F =(n g -n F ) / (n F -n C (1)
[0056] In some embodiments, the partial dispersion ratio (P0) of the high-refractive-index, high-dispersion optical glass of this application is... g,F The lower limit is 0.6050, and the optional lower limit is 0.6070.
[0057] In some embodiments, the partial dispersion ratio (P0) of the high-refractive-index, high-dispersion optical glass of this application is... g,F The maximum value is 0.6200, and the optional maximum value is 0.6180.
[0058] Anti-crystallization properties
[0059] The resistance to crystallization of glass was tested using the following methods:
[0060] The glass to be tested was processed into a sample with dimensions of 20mm×20mm×10mm, polished on both sides, and then placed in a container at a temperature of T. g Hold the glass in a crystallization furnace at +200℃ for 30 minutes. After cooling, polish both surfaces. Judge the crystallization performance of the glass according to the table below, with Grade A being the best and Grade E being the worst.
[0061] Table 1. Grading and Judgment Criteria for Crystallization
[0062]
[0063] In some embodiments, the anti-crystallization performance of the high-refractive-index, high-dispersion optical glass of this application is grade B or above, and can be selected as grade A.
[0064] <Coefficient of thermal expansion>
[0065] The coefficient of thermal expansion of optical glass (α) 100℃ / 300℃ The coefficient of thermal expansion at 100℃~300℃ was tested according to the method specified in the national standard GB / T7962.16—2010.
[0066] In some embodiments, the thermal expansion coefficient (α) of the high-refractive-index, high-dispersion optical glass of this application is... 100℃ / 300℃ ) is 80×10 -7 / K~120×10 -7 / K, optional 85×10 -7 / K~115×10 -7 / K, or 90×10 -7 / K~110×10 -7 / K.
[0067] <Stability under acid conditions>
[0068] Acid resistance stability of optical glass (D) A (Powder method) Tested according to the method specified in GB / T 17129.
[0069] In some embodiments, the acid resistance stability (D) of the high-refractive-index, high-dispersion optical glass of this application is... A If there are two or more categories, one category can be selected.
[0070] <Stability under water resistance>
[0071] Water resistance stability of optical glass (D) W (Powder method) Tested according to the method specified in GB / T 17129.
[0072] In some embodiments, the water resistance stability (D) of the high-refractive-index, high-dispersion optical glass of this application is... W If there are two or more categories, one category can be selected.
[0073] <Transition Temperature>
[0074] Transition temperature of optical glass (T) g Test according to the method specified in the national standard GB / T7962.16—2010.
[0075] In some embodiments, the transition temperature (Ti) of the high-refractive-index, high-dispersion optical glass of this application is... gThe temperature is below 610℃, and can be selected as below 600℃, or even below 590℃.
[0076] <Density>
[0077] The density (ρ) of optical glass is tested according to the method specified in the national standard GB / T7962.20—2010.
[0078] In some embodiments, the density (ρ) of the high-refractive-index, high-dispersion optical glass of this application is 3.80 g / cm³. 3 The following can be selected as 3.70 g / cm³. 3 The following is an alternative option: 3.60 g / cm³ 3 the following.
[0079] <Colorization>
[0080] The short-wavelength transmission spectral characteristics of the optical glass in this application are expressed using tinting luminance (λ). 70 ) represents. λ 70 This refers to the wavelength corresponding to a glass transmittance of 70%. λ 70 The measurement was performed using a glass with a thickness of 10 ± 0.1 mm and two optically polished, parallel planes. The spectral transmittance was measured in the wavelength range from 280 nm to 700 nm, and wavelengths exhibiting 70% transmittance were recorded. Spectroscopic transmittance, or transmittance, is the value of transmittance when an intensity I is incident perpendicularly onto the aforementioned surface of the glass. in Light passes through the glass and exits from a plane with an intensity of I. out In the case of light, through I out / I in The value represents the transmittance, which also includes the surface reflection loss on the aforementioned surfaces of the glass. The higher the refractive index of the glass, the greater the surface reflection loss. Therefore, λ 70 A low value means that the glass itself has very little coloration and high light transmittance.
[0081] In some embodiments, the chromaticity (λ) of the high-refractive-index, high-dispersion optical glass of this application... 70 The wavelength is below 430nm, and can be selected as below 425nm, or even below 420nm.
[0082] <Effervescence>
[0083] The bubble degree of optical glass is tested according to the method specified in the national standard GB / T7962.8—2010.
[0084] In some embodiments, the bubble degree of the high-refractive-index, high-dispersion optical glass of this application is grade A or above, optionally grade A0 or above, and more preferably grade A. 00 class.
[0085] Manufacturing method of high refractive index and high dispersion optical glass
[0086] The manufacturing method of the high-refractive-index, high-dispersion optical glass of this application is as follows: The glass of this application is produced using conventional raw materials and processes, including but not limited to using oxides, hydroxides, complex salts (such as carbonates, nitrates, sulfates, phosphates, metaphosphates, etc.), boric acid, etc. as raw materials. After the raw materials are prepared according to conventional methods, the prepared furnace charge is put into a melting furnace (such as a platinum or platinum alloy crucible) at 1000℃~1400℃ for melting. After clarification and homogenization, a homogeneous molten glass without bubbles and undissolved substances is obtained. This molten glass is then cast in a mold and annealed. Those skilled in the art can appropriately select raw materials, process methods, and process parameters according to actual needs.
[0087] [Glass preforms and optical components]
[0088] High-refractive-index, high-dispersion optical glass can be used to fabricate glass preforms using methods such as direct drop forming, grinding, or hot pressing. Specifically, glass preforms can be fabricated by directly and precisely drop-forming molten optical glass into precision glass preforms, by machining such as grinding and polishing, or by hot pressing a preform made from optical glass for compression molding followed by grinding. It should be noted that the methods for preparing glass preforms are not limited to the methods described above.
[0089] As described above, the high refractive and high dispersion optical glass of this application is useful for various optical components and optical designs. In particular, a preform can be formed from the high refractive and high dispersion optical glass of this application, and the preform can be used for hot pressing, precision stamping, etc., to manufacture optical components such as lenses and prisms.
[0090] Both the glass preform and the optical element in this application are formed from the high-refractive-index, high-dispersion optical glass described above. The glass preform of this application possesses the excellent properties of optical glass; the optical element of this application possesses the excellent properties of high-refractive-index, high-dispersion optical glass, and can provide various optical elements such as lenses and prisms with high optical value.
[0091] Examples of lenses include concave meniscus lenses, convex meniscus lenses, biconvex lenses, biconcave lenses, plano-convex lenses, plano-concave lenses, and so on, where the lens surface is spherical or aspherical.
[0092] [Optical Instruments]
[0093] The optical elements formed from the high-refractive-index and high-dispersion optical glass of this application can be used to manufacture optical instruments such as photographic equipment, video equipment, projection equipment, display equipment, automotive equipment, and monitoring equipment.
[0094] Example
[0095] <Examples of High-Refractive-Intensity High-Dispersion Optical Glass>
[0096] To further illustrate and explain the technical solution of this application, the following non-limiting embodiments are provided.
[0097] In this embodiment, high-refractive-index, high-dispersion optical glass with the compositions shown in Tables 2 to 4 was obtained using the manufacturing method described above. Furthermore, the properties of each glass were measured using the testing method described in this application, and the measurement results are shown in Tables 2 to 4.
[0098] Table 2.
[0099]
[0100] Table 3.
[0101]
[0102] Table 4.
[0103]
[0104] <Example of Glass Prefabricated Components>
[0105] The glass obtained from Examples 1 to 20# of high-refractive-index and high-dispersion optical glass is used to manufacture preforms of various lenses and prisms, such as concave meniscus lenses, convex meniscus lenses, biconvex lenses, biconcave lenses, plano-convex lenses, and plano-concave lenses, by means such as grinding, hot pressing, precision stamping, etc.
[0106] <Optical Component Examples>
[0107] Annealing these preforms obtained from the above glass preform examples reduces internal stress in the glass while fine-tuning the refractive index, so that optical properties such as the refractive index reach the desired values.
[0108] Next, the prefabricated parts are ground and polished to produce various lenses and prisms, such as concave meniscus lenses, convex meniscus lenses, biconvex lenses, biconcave lenses, plano-convex lenses, and plano-concave lenses. Anti-reflective coatings can also be applied to the surface of the resulting optical elements.
[0109] <Examples of Optical Instruments>
[0110] The optical elements obtained from the above-described optical element embodiments can be used, through optical design, to form optical components or optical assemblies by using one or more optical elements. These components can be used in, for example, imaging devices, sensors, microscopes, medical technology, digital projection, communications, optical communication technology / information transmission, optics / lighting in the automotive field, lithography technology, excimer lasers, wafers, computer chips, and integrated circuits and electronic devices that include such circuits and chips.
Claims
1. A high-refractive-index, high-dispersion optical glass, characterized in that, Its composition, expressed as a weight percentage, contains: SiO2: 15%–35%; Nb2O5: 33%–55%; Na2O: 2%–10%; ZrO2: 2%–10%; TiO2: 2%–12%; Li2O: 0–10%; ZnO: greater than 0 but less than or equal to 5%, wherein ZnO / (Na2O+Li2O) is 0.02–0.
35.
2. The high-refractive-index, high-dispersion optical glass according to claim 1, characterized in that, Its components, expressed as a weight percentage, also contain: P2O5: 0–5%; and / or RO: 0–5%; and / or K2O: 0–5%; and / or WO3: 0–5%; and / or Re2O3: 0–1%; and / or clarifying agent: 0–1%, wherein the RO is one or more of MgO, CaO, SrO, and BaO, the Re2O3 is one or more of La2O3, Y2O3, and Gd2O3, and the clarifying agent is one or more of Sb2O3, SnO, SnO2, and CeO2.
3. A high-refractive-index, high-dispersion optical glass, characterized in that, Its composition includes SiO2, Nb2O5, Na2O, ZrO2, TiO2, and ZnO, expressed as a weight percentage. It contains 0–10% Li2O, with a ZnO / (Na2O+Li2O) ratio of 0.02–0.
35. The refractive index n of the high-refractive-index, high-dispersion optical glass is... d The Abbe number ν ranges from 1.82 to 1.
89. d The stability of the acid resistance is 21-28. A Class 2 or above, water resistance stability D W It is classified as category 2 or above.
4. The high-refractive-index, high-dispersion optical glass according to claim 3, characterized in that, Its components, expressed as a weight percentage, contain: SiO2: 15%–35%; and / or Nb2O5: 33%–55%; and / or Na2O: 2%–10%; and / or ZrO2: 2%–10%; and / or TiO2: 2%–12%; and / or ZnO: greater than 0 but less than or equal to 5%; and / or P2O5: 0–5%; and / or RO: 0–5%; and / or K2O: 0–5%; and / or WO3: 0–5%; and / or Re2O3: 0–1%; and / or clarifying agent: 0–1%, wherein the RO is one or more of MgO, CaO, SrO, and BaO, the Re2O3 is one or more of La2O3, Y2O3, and Gd2O3, and the clarifying agent is one or more of Sb2O3, SnO, SnO2, and CeO2.
5. The high-refractive-index, high-dispersion optical glass according to any one of claims 1 to 4, characterized in that, Its components are expressed as a weight percentage and satisfy one or more of the following conditions: 1) ZnO / (Na2O+Li2O) is 0.05~0.30, and ZnO / (Na2O+Li2O) can be 0.06~0.27; 2) The TiO2 / Nb2O5 ratio is 0.05 to 0.30, and can be selected as 0.08 to 0.27, or even more preferably 0.10 to 0.24; 3) The ratio of (TiO2+Nb2O5) / (SiO2+ZrO2+ZnO) is 0.75~2.50, and optionally (TiO2+Nb2O5) / (SiO2+ZrO2+ZnO) is 0.80~2.20, and even more preferably (TiO2+Nb2O5) / (SiO2+ZrO2+ZnO) is 1.11~1.96; 4) The ratio of (P2O5+ZnO) / SiO2 is 0.01 to 0.35, and can be selected as 0.02 to 0.30, or even more preferably 0.04 to 0.
24.
6. The high-refractive-index, high-dispersion optical glass according to any one of claims 1 to 4, characterized in that, Its components are expressed as weight percentages, including: SiO2: 17%–33%, optionally SiO2: 18%–30%; and / or Nb2O5: 34%–53%, optionally Nb2O5: 35%–50%; and / or Na2O: 3%–9%, optionally Na2O: 4%–8%; and / or ZrO2: 3%–9%, optionally ZrO2: 4%–8%; and / or TiO2: 3%–11%, optionally TiO2: 4%–10%; and / or Li2O: 1%–9%, optionally Li2O: 2%–7%; and / or ZnO: 0.2%–4%, optionally ZnO: 0.5%–3%; and / or P2O5: 0.2%–3%. The following are optional components: P2O5: 0.3%–2%; and / or RO: 0–4%, optional RO: 0–3%; and / or K2O: 0–4%, optional K2O: 0–3%; and / or WO3: 0–4%, optional WO3: 0–3%; and / or Re2O3: 0–0.8%, optional Re2O3: 0–0.5%; and / or clarifying agent: 0–0.5%, optional clarifying agent: 0–0.2%, wherein the RO is one or more of MgO, CaO, SrO, and BaO, the Re2O3 is one or more of La2O3, Y2O3, and Gd2O3, and the clarifying agent is one or more of Sb2O3, SnO, SnO2, and CeO2.
7. The high-refractive-index, high-dispersion optical glass according to any one of claims 1 to 4, characterized in that, The refractive index n of the high-refractive-index, high-dispersion optical glass d The range is 1.82–1.89, with an optional range of 1.83–1.88, and even more preferably 1.84–1.87; and / or the Abbe number ν. d The value is 21–28, optionally 22–27, and even more preferably 23–26; and / or acid resistance stability D. A If there are two or more categories, one category may be selected; and / or water resistance stability D W If there are two or more classes, one class can be selected; and / or partial dispersion ratio P g,F The coefficient of thermal expansion is 0.6050–0.6200, and can be selected as 0.6070–0.6180; and / or the anti-crystallization performance is grade B or above, and can be selected as grade A; and / or the coefficient of thermal expansion α 100℃ / 300℃ 80×10 -7 / K~120×10 -7 / K, optional 85×10 -7 / K~115×10 -7 / K, or 90×10 -7 / K~110×10 -7 / K; and / or transition temperature T g Temperature is below 610℃, optionally below 600℃, and even more preferably below 590℃; and / or density ρ is 3.80 g / cm³. 3 The following can be selected as 3.70 g / cm³. 3 The following is an alternative option: 3.60 g / cm³ 3 The following; and / or chromaticity λ 70 The wavelength is below 430nm, optionally below 425nm, and even more preferably below 420nm; and / or the bubble density is A grade or above, optionally above A0 grade, and even more preferably A. 00 class.
8. A glass precast component, characterized in that, It is made of the high refractive and high dispersion optical glass as described in any one of claims 1 to 7.
9. An optical element, characterized in that, It is made of high-refractive-index, high-dispersion optical glass as described in any one of claims 1 to 7, or of glass preform as described in claim 8.
10. An optical instrument, characterized in that, It contains the high-refractive-index, high-dispersion optical glass according to any one of claims 1 to 7, and / or contains the optical element according to claim 9.